Hippocampal Amyloid Burden with Downstream Fusiform Gyrus Atrophy Correlate with Face Matching Task Scores in Early Stage Alzheimer’s Disease - Chang, Ya-Ting; Huang, Chi-Wei; Chen, Nai-Ching; Lin, Kun-Ju; Huang, Shu-Hua; Chang, Wen-Neng; Hsu, Shih-Wei; Hsu, Che-Wei; Chen, Hsiu-Hui; Chang, Chiung-Chih (Frontiers in Aging Neuroscience, 2016)
Purpose: Neuronal activity during face matching shows co-activation of the fusiform gyrus (FG) and areas along the ventral visual network. To elucidate the role of β-amyloid (Aβ) deposition in relation to gray matter (GM) atrophy within the ventral visual network, it is crucial to delineate the pathological mechanisms of Alzheimer’s disease (AD) on facial discrimination. Methods: Comprehensive cognitive assessments and GM analysis by using magnetic resonance imaging and AV-45 positron emission tomography (PET) were studied in 44 patients with AD. We used AV-45 PET to measure regional Aβ to analyze the correlations between the regional neocortical AV-45 retention and atrophy in patients with AD. Results: FG volume was positively correlated with the para-hippocampus (β = 0.565, P < 0.001), posterior cingulate cortex (PCC) (β = 0.402, P < 0.001), and hippocampus volumes (β = 0.209, P = 0.044). After carefully confounded all possible factors simultaneously, the hippocampus standardized uptake value ratio (SUVr) was independently associated with FG volume (β = -0.151, P = 0.017). Furthermore, volumes of the hippocampus (r = 0.473, P = 0.003), para-hippocampus (r = 0.515, P = 0.001), and FG (r = 0.383, P =0.018) were associated with Benton’s facial recognition test. Conclusions: In conclusion, our study indicates that amyloid burden within the hippocampus may contribute to FG cortical hub GM atrophy. While the face matching task scores were related to the FG, hippocampus, and para-hippocampus volumes, concordant changes of the aforementioned three structures suggested the importance of the three ventral visual network hubs in AD.